Profile of Scabies in Surabaya Boarding School - Widyantari, Septiana; Rozita Maharani, Dinda; Muhammad Yulianto Listiawan (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2023)
Background: Scabies is a skin infection caused by infection and susceptibility to the variant mite Sarcoptes scabiei hominis and its derivatives. Scabies disease can be transmitted through direct contact with mites and causes itching on the human body, which can develop into secondary infections. Purpose: to determine the characteristics of scabies according to age, location of lesions, and signs of lesions in students of Surabaya Boarding School on December 2021. Methods: This study is a cross-sectional descriptive study with data collection through interviews and clinical examinations. Results: Scabies included 40 cases out of 86 respondents. Scabies cases occurred in boys aged between 13 and 15 (37%). The largest proportion of lesions were found all over the body, including between the fingers (75%), between the fingers and arms (15%), between the toes and legs (7%), and underarms (3%). The most common lesions were erythema papules and crusts in 57%, erythema papules, pustules, and crusts in 28%, and erythematous macules only in 18%. Conclusion: The importance of education for children about scabies, personal hygiene behavior, environmental hygiene, and other variables that affect the incidence of scabies. It is important that all affected household members are treated and their living environment properly disinfected to ensure tick removal and ultimately prevent further transmission.